Sociedade civil e democracia: o grupo de visegrado em perspetiva comparada - Duarte, M. C. (2020)
This article aims to understand the influence of civil society on the quality of democracy in the Visegrad Group countries (Slovakia, Hungary, Poland and the Czech Republic). To do so, the evolution of civil society in these countries was mapped, and the main theoretical debates on the theme were mobilised. Using data from international surveys over three different periods of time, it was found that citizen adherence to voluntary civil society organizations is weak in the four countries. These differences notwithstanding, the Czech Republic presents the best levels of participation in voluntary organizations, while Poland displays the worst. When analysing the relationship between civil society, volunteering associations and democracy, it can be concluded that, even though these countries may be facing a democratic setback, it should not be attributed to the weak levels of citizen participation in volunteering associations.